2020
DOI: 10.3390/su122410277
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Confucius Institutes and One Belt, One Road Initiatives on the Values of Cross-Border M&A: Empirical Evidence from China

Abstract: This study examines how national cultural policies such as Confucius Institutes and One Belt, One Road initiatives (BRI) affect the post-acquisition returns of Chinese cross-border mergers and acquisitions based on data from a sample of 192 transactions covering 2011 to 2015. We find that the cultural export of Chinese Confucius Institutes and the BRI exert a significantly positive impact on long-term acquirer returns, while cultural/institutional distance exerts a negative impact. Further evidence shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This includes constructing and renovating museums, theatres, cultural centres, and heritage sites. These infrastructure developments not only improve cultural accessibility but also serve as platforms for cultural exchanges, performances, and exhibitions, thereby bolstering cultural diplomacy efforts (Jung et al, 2020). The Chinese government has also actively promoted cultural diplomacy and educational cooperation through these cultural infrastructures.…”
Section: China's Attempts and Achievements In Cultural Diplomacy In T...mentioning
confidence: 99%
“…This includes constructing and renovating museums, theatres, cultural centres, and heritage sites. These infrastructure developments not only improve cultural accessibility but also serve as platforms for cultural exchanges, performances, and exhibitions, thereby bolstering cultural diplomacy efforts (Jung et al, 2020). The Chinese government has also actively promoted cultural diplomacy and educational cooperation through these cultural infrastructures.…”
Section: China's Attempts and Achievements In Cultural Diplomacy In T...mentioning
confidence: 99%
“…From the current research on financing constraints and cross-border M&As, scholars agree that financing constraints may hinder and restrict firms' cross-border M&As, and the alleviation of financing constraints will promote cross-border M&As [84]. Firms with strong financing capacities and firms with low financing constraints are more inclined to choose cross-border M&As.…”
Section: Intermediation Of Financing Constraintsmentioning
confidence: 99%
“…e previous study on the four influencing factors of accounting conservatism, including contract, tax, litigation, and supervision, found that the debt contract and compensation contract in the contract factor, the tax burden corresponding to the tax factor, and the legal system corresponding to the litigation and regulatory factors can all effectively explain the differences in the quality of accounting information of enterprises. Based on existing studies [28][29][30], it can be argued that the BRI influences the energy-intensive corporate accounting decisions through four channels that affect corporate debt contracts, executive compensation, the tax burden, and the legal environment.…”
Section: Eoretical Framework and Research Hypothesismentioning
confidence: 99%